2019
DOI: 10.1017/s1751731119001617
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of mortality in pre-weaning kids of Sirohi goat

Abstract: Pre-weaning animals exit a flock through death induced by various reasons, causing significant economic losses to the goat producers. In this study, we investigated the survival from birth to weaning of Sirohi goat kids within framework of the survival analysis. Kid records were accessed from 1997 to 2017, with the information on 4417 pre-weaning animals of farmed Sirohi goat native to the Rajasthan State of India. A multivariable Cox regression was fitted to the data after checking the assumptions of regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 25 publications
6
36
1
Order By: Relevance
“…At Condobolin, 62% of all perinatal kid losses in Australian rangeland and crossbred goats occurred when the chill index was above 950 kJ/m 2 .h (Bajhau and Kennedy 1990). In semi-intensively managed Sirohi goats in India, winter kidding has been associated with 2.2 times higher risk of mortality than kidding in other seasons (Chauhan et al 2019). Birthing in milder months will reduce the risk of mortality associated with exposure (Broster et al 2012).…”
Section: Starvation Mismothering and Exposurementioning
confidence: 99%
“…At Condobolin, 62% of all perinatal kid losses in Australian rangeland and crossbred goats occurred when the chill index was above 950 kJ/m 2 .h (Bajhau and Kennedy 1990). In semi-intensively managed Sirohi goats in India, winter kidding has been associated with 2.2 times higher risk of mortality than kidding in other seasons (Chauhan et al 2019). Birthing in milder months will reduce the risk of mortality associated with exposure (Broster et al 2012).…”
Section: Starvation Mismothering and Exposurementioning
confidence: 99%
“…A strong correlation between and speed of growth was found during the first year. Several studies have found that kids (or lambs) with the lowest weight have a lower chance of survival (Riggio et al, 2008;Dwyer et al, 2016;Chauhan et al, 2019) that could be partly attributed to the increased risk of hypothermia, which has been related to size as well as the individual's fat reserves (Alexander, 1962). Moreover, smaller kids are penalized in all aspects of social competition.…”
Section: Discussionmentioning
confidence: 99%
“…Stillborn kids were a problem to rst time does during year-1. Stillborn kids are usually exposed to infections like toxoplasmosis, brucellosis, chlamydiosis or leptospirosis (Chauhan et al, 2019). Kids suffering from these infections are normally born weak and die shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates of kids from birth to weaning is one of the prime effects on the viability of goat production e ciency in communal areas (Perumal et al, 2019;Yasmin et al, 2020), with kid mortality rates as high as 46.51 % having been reported in various farming communities across South Africa (Sebei et al, 2004;Slayi et al, 2014). The untimely exits restrict the number of animals available for future replacement and impact the number of animals reaching marketable age (Chauhan et al, 2019). Increased kid mortality rate is sometimes attributed to genetic and environmental factors (Alemnew et al, 2020;Perumal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%